Російськомовні елементи в дискурсі сучасної української преси як інтертекстуальні одиниці - Трифонов, Р.А.; Логвінова, О.В. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2006)
В статье рассмотрена интертекстуальная природа русскоязычных элементов в современной украинской периодике, выделены типы дискурсов и прецедентных текстов, из которых происходят эти единицы. The article considers the intertextual nature of Russian language elements in modern Ukrainian press. The types of discourses and precedent texts - the sources of such units - are determined and classified.
Keywords: українська преса; двомовність; білінгвізм; русизми